Impact of macroeconomic news on metal futures - Elder, John, author; Miao, Hong, author; Ramchander, Sanjay, author; Journal of Banking & Finance, publisher (Colorado State University. Libraries, 2011)
This paper uses intra-day data for the period 2002 through 2008 to examine the intensity, direction, and speed of impact of U.S. macroeconomic news announcements on the return, volatility and trading volume of three important commodities – gold, silver and copper futures. We find that the response of metal futures to economic news surprises is both swift and significant, with the 8:30 am set of announcements – in particular, nonfarm payrolls and durable goods orders – having the largest impact. Furthermore, announcements that reflect an unexpected improvement in the economy tend to have a negative impact on gold and silver prices; however, they tend to have a positive effect on copper prices. In comparison, realized volatility and volume for all three metals are positively influenced by economic news. Finally, there is evidence that several news announcements exert an asymmetric impact on market activity variables.
Published as: Journal of Banking & Finance, vol.36, no. 1, pp.51-65, January 2012, https://doi.org/10.1016/j.jbankfin.2011.06.007.
Keywords: macroeconomic news; metal futures; return; volatility; volume